Role for Conservative Management in Grade V Renal Trauma. Issue 3 (7th March 2023) - Hakam, Nizar; Shaw, Nathan M.; Lui, Jason; Abbasi, Behzad; Myers, Jeremy B.; Breyer, Benjamin N.
Abstract : Purpose: We assessed the use of conservative management for American Association for the Surgery of Trauma grade V renal trauma in the National Trauma Databank. Materials and Methods: We used data of grade V renal trauma patients in the 2017-2019 National Trauma Databank. Conservative management was defined by the absence of surgical or procedural intervention except for ureteral stent or percutaneous drain placement. We initially analyzed patients who survived to final hospital discharge and reported the percent utilization of conservative management. We then repeated our analysis in the overall grade V population and in all those who did not die in the emergency department. Results: Of 1, 474 who survived to discharge, 557 (37.8%) patients were managed conservatively. In the adjusted analysis, penetrating trauma mechanism (OR 0.13, 95% CI 0.09-0.19, P < .001) and receiving transfusion (OR 0.22, 95% CI 0.17-0.29, P < .001) were associated with decreased odds of receiving conservative management. Overall, there were 1, 919 patients with grade V injury, of whom 731 (38.1%) were managed conservatively. Mortality rate was 22.8% in those managed conservatively vs 23.8% in those who had intervention. After excluding 110 patients who died in the emergency department, there were 1, 809 patients, of whom 625 (34.6%) were managed conservatively. Mortality rate was 22.6% in the operatively managed group and 10.9% in the conservatively managed group. Conclusions: A substantial portion of grade V renal trauma cases were managed successfully without intervention in the National Trauma Databank. Further research is needed to identify radiological phenotypes suitable for nonoperative management and to overcome possible renal trauma grade misclassification.